The Power of Weather. Some Empirical Evidence on Predicting Day-Ahead Power Prices Through Weather Forecasts - Christian Huurman; Francesco Ravazzolo; Chen Zhou (Norges Bank, 2008)
This paper examines the predictive power of weather for electricity prices in day-ahead markets in real time. We find that next-day weather forecasts improve the forecast accuracy of day-ahead electricity prices substantially, suggesting that weather forecasts can price the weather premium. Moreover, we find that the predictive power of weather forecasts for electricity prices can be further exploited by allowing for non-linear effects of the weather forecasts.
hdl:11250/2497777
Keywords: C53; G15; Q40; 330; GARCH models; electricity prices; forecasting; weather forecasts